Discovery of a new species of Caloptilia (Lepidoptera: Gracillariidae) from east and central Africa with its suggested associated host (Gentianales: Rubiaceae) and natural enemies (Hymenoptera: Eulophidae) - de Prins, Jurate; Gumovsky, Alex; Coninck, Eliane De (Zootaxa, 2015)
A new species of the leaf-mining moth genus Caloptilia (Gracillariidae), C. mwamba sp. nov., suggested to be associated with Cremaspora triflora (Thonn.) K.Schum. (Rubiaceae) is described from east and central Africa. The taxonomic relationships of the new species with its congeners from the Oriental and the Palaearctic regions are discussed. Newly obtained taxonomic and biological data are linked with the DNA barcode workbench in BOLD, providing the molecular, machine-readable identification tag of the new species. New distribution and morphological data for two parasitoid species, Afrotroppopsis risbeci Gumovsky, 2007 and Zaommomentedon newbyi (Kerrich, 1969) (Eulophidae), which were found to be associated with C. mwamba sp. nov., are presented.